Estimation of ultrasound reference values for the ulnar nerve fascicular number and cross-sectional area in young males: A cross-sectional study - Bedewi, Mohamed Abdelmohsen (Medicine (Baltimore), 2017)
The objective of this study is to estimate the reference values for the number of fascicles and cross-sectional area (CSA) of the ulnar nerve at a single predetermined site by ultrasound in healthy young adult males. The demographic and physical characteristics of 50 adult male volunteers were evaluated and recorded. The subjects were positioned supine with the elbow flexed at 90° and the palm of the hand placed on a hard surface. The ulnar nerve was scanned bilaterally 1 cm proximal to the medial epicondyle in projection of the cubital tunnel. The number of fascicles and mean CSA of the ulnar nerve were identified. In addition, the side-to-side differences of the estimated reference values and their correlations with the age, weight, height, and body mass index (BMI) were evaluated. The mean fascicular number was 5.66 ± 1.48, the mean ultrasound-estimated CSA of the ulnar nerve was 6.54 ± 1.67 mm(2) and both sides were comparable in the mean CSA and fascicular number (6.43 ± 1.80 mm(2) and 5.88 vs 6.64 ± 1.55 mm(2) and 5.44, for right and left side, respectively). No significant correlations were observed between CSA and fascicles number and age, weight, height, or BMI of study subjects. The reference values for the number of fascicles number and the CSA of the ulnar nerve at a single predetermined site were identified. These values could be used for the sonographic diagnosis and follow-up of the ulnar nerve lesions.